2005
DOI: 10.1086/432733
|View full text |Cite
|
Sign up to set email alerts
|

A Case‐Control Study to Examine HLA Haplotype Associations in Patients with Posttreatment Chronic Lyme Disease

Abstract: In a comparison of 95 patients with systemic symptoms that persisted after antibiotic treatment for acute Lyme disease (posttreatment chronic Lyme disease) and 104 control subjects without such symptoms after antibiotic treatment, we sought associations between human leukocyte antigen class II (DRB1 and DQB1) markers and posttreatment chronic Lyme disease. No strong association between posttreatment chronic Lyme disease and any class II allele or genotype was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
8
1
Order By: Relevance
“…The genotypes of the infecting strains of B. burgdorferi were unknown in the Klempner et al study, but, presumably, some of the patients were infected with RST3 strains. Nevertheless, the carriage rate of the DRB1*0101 allele was significantl greater in the patients infected with RST3 strains in the present study, compared with that in patients with Lyme disease in the study by Klempner et al (9/25 vs. 12/95; ) [14]. P p .015 A statistical adjustment for multiple comparisons is controversial in studies evaluating associations between infectious diseases and HLA haplotypes and alleles [25,26], and no adjustment was performed in the present study.…”
contrasting
confidence: 72%
See 2 more Smart Citations
“…The genotypes of the infecting strains of B. burgdorferi were unknown in the Klempner et al study, but, presumably, some of the patients were infected with RST3 strains. Nevertheless, the carriage rate of the DRB1*0101 allele was significantl greater in the patients infected with RST3 strains in the present study, compared with that in patients with Lyme disease in the study by Klempner et al (9/25 vs. 12/95; ) [14]. P p .015 A statistical adjustment for multiple comparisons is controversial in studies evaluating associations between infectious diseases and HLA haplotypes and alleles [25,26], and no adjustment was performed in the present study.…”
contrasting
confidence: 72%
“…The primary purpose was to serve as a control group of patients who had recovered from Lyme disease in an evaluation of whether the HLA class II haplotype was associated with the development of PTCLD. The results of that investigation were described elsewhere [14]. The secondary purpose was to determine whether HLA class II alleles are associated with infection with strains from specifi genotypes of B. burgdorferi.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There has been little research in the role of autoimmunity in post-Lyme disease syndrome, but one study showed no association between a class II allele or genotype [51].…”
Section: The Possible Causes Of Post-lyme Disease Symptomsmentioning
confidence: 99%
“…The follow-up study by Klempner et al reported in this issue of The Journal of Infectious Diseases [20] has provided another piece to this complex puzzle by helping to rule out an autoimmune mechanism in PTCLD. Using banked samples from their treatment cohorts and matched samples from asymptomatic subjects who were treated for LD, these researchers were unable to establish a clear link between treatment outcome and HLA haplotype.…”
mentioning
confidence: 99%